2009
DOI: 10.1089/lap.2008.0292
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Recurrence Rate in the Laparoscopic Herniorraphy in Children: Comparison Between Two Techniques

Abstract: In our experience, the incision of the peritoneum lateral to the internal inguinal ring and the W-shaped suture, compared to the sole W-shaped suture, is safe and effective in preventing hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Marte et al stated that the incision of the peritoneum lateral to the internal inguinal ring and the W-shaped suture, compared to the sole W-shaped suture, is safe and effective in preventing hernia recurrence [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marte et al stated that the incision of the peritoneum lateral to the internal inguinal ring and the W-shaped suture, compared to the sole W-shaped suture, is safe and effective in preventing hernia recurrence [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, transient or persistent hydrocele was unavoidable after these laparoscopic techniques. Tsai et al and others dissected and transected the neck of the sac at IIR to be followed by a suture closure, with this being a faithful reproduction of the inguinal approach [2426]. They claimed that leaving the hernial sac in continuity without disconnection at IIR may be the cause of subsequent recurrence and hydrocele formation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Shalaby et al had reported a lower recurrence rate (0.8 %) after laparoscopic repair by RN and 2.4 % recurrence after open herniotomy [15]. Avoiding the gonadal vessels and vas deferens during subcutaneous endoscopic ligation may leave a small gap in the IIR [9,17,18]. And an important step of transecting the sac in open herniotomy is not achieved in many laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…And an important step of transecting the sac in open herniotomy is not achieved in many laparoscopic techniques. The skip areas in the IIR and leaving the sac in continuity without disconnection may be the cause of subsequent recurrence of hernia and hydrocele formation in the postoperative period [9,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has seen a significant controversy concerning the value of laparoscopic hernia repair in children. However, the literature has recently contained an increasing number of reports on laparoscopic hernia repair in children, highlighting an increase not only in the number of cases that have been managed but also in the number of modifications and technical refinements in the procedure itself [2][3][4][5][6][7][8][9][10][11]. To the best of our knowledge, our study represents the largest series to date of infants weighing 5 kg or less who had inguinal hernias repaired via laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%